QM-MM investigation on chorismate synthase enzyme role - Lawan,N. (Chiang Mai University, 2015)
Chorismate is a key intermediate in the biosynthesis of many aromatic compounds, including the aromatic amino acids. Chorismate synthase (CS) is an enzyme responsible for the biosynthesis of chorismate. Although several proposals have been made, the role of this enzyme is still unclear. In this work, therefore, the QM-MM adiabatic mapping calculations at the AM1-CHARMM27 level were performed. The comparisons between potential energy surface (PES) of reaction in enzyme (QM-MM energy) and the PES of reaction without enzyme (QM energy) were made. The results showed that the first step of the reaction mechanism is proton transfer rather than phosphate elimination. Several mechanisms have been proposed that the CS enzyme stabilized transition state to catalyze the reaction. This work, however, observed that not only was transition state stabilized but also intermediate and product. In addition, the enzyme holds substrate and cofactor together in the appropriate orientation making the reaction easier to proceed.